Addressing the prophets in the Holy Quran between science and metaphor (Journal of the College of Basic Education, 2023)
The Holy Qur’an, as Muslims and non-Muslims know it, is a sea full of everything, or as it is said, it came upon every small and large part of human life. I hope to win the pleasure of God, may God’s prayers and peace be upon them, and provide what they were able to provide of service to this great book. ) is known in Arabic grammar or by the nickname (the title), or the metaphor. I was impressed by this distinction between the number of addresses that were mentioned in the great book, so I studied it with great care and accuracy, hoping for that access and identification of the reasons for this distinction in the speech of God - peace be upon him - to all His prophets - may God bless him and grant him peace. I have succeeded in this work, and from God is help and strength.I divided the research into two chapters. In the first, I dealt with (science) and its divisions, and how the Holy Book of God dealt with the names of all the prophets , and the second included metaphors and the difference between them and nicknames, and how God, may He be glorified and exalted be He, addresses them, based on their nicknames in general or by picking up some specific metaphors, so I hope for him From God  acceptance and success.